Kedudukan Hukum Objek Hak Atas Tanah Atas Perjanjian Pelepasan Hak Atas Tanah Yang Bayar Secara Cicilan - Sihite, Sri Rumada (Postgraduate Program Doctoral in Law, Universitas Pattimura, 2022)
Introduction: Agreement on the transfer of land rights number 04/L/GGPG/IX/2013 dated September 11, 2013 which became the issue raised by the author. The agreement made in the letter of agreement is a default between the parties who are considered to have owned the land, but it is interesting to see the legal position of the object of land rights on the agreement to release land rights which is paid in installments (study of the supreme court decision 2875/k/pdt/2016. Purposes of the Research: to answer how the legal position of the object of the right to the agreement to release the right to be paid in installments (study of the supreme court decision 2875k/pdt/2016. Methods of the Research: The type of research used is normative juridical research. The nature of this research is descriptive. The data source used is secondary data. The nature of this research is descriptive analytical research and drawing conclusions using deductive methods. Results Originality of the Research: The position of the land object is on the seller's side because the conditions for the transfer of the object of land rights to the buyer are not valid in accordance with the provisions of the agrarian law, namely the legal requirements for registering the transfer of land rights.